2018
DOI: 10.1111/deci.12307
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility (CSR) Issues in Supply Chain Competition: Should Greenwashing Be Regulated?

Abstract: Corporate social responsibility (CSR) has been treated as an instrument to differentiate firms in a competitive market. However, due to the credence good nature of CSR, when considering product quality dimension, firms can only signal their quality through advertising or labeling. These signaling mechanisms may be exploited by some dishonest firms who claim to be green (“greenwashing”). Many critics argue that greenwashing needs to be regulated because it deceives the market and discourages firms from going ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 54 publications
1
50
0
Order By: Relevance
“…Under the supply chain environment, CSR is especially important to meet business needs [21]. That is because that CSR affects not only the purchase intention of consumer [7] but also the social reputations of firms [22,23]. Therefore, CSR has emerged frequently under supply chain environment.…”
Section: Csrmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the supply chain environment, CSR is especially important to meet business needs [21]. That is because that CSR affects not only the purchase intention of consumer [7] but also the social reputations of firms [22,23]. Therefore, CSR has emerged frequently under supply chain environment.…”
Section: Csrmentioning
confidence: 99%
“…It is shown that 70% of consumers would like to pay an extra price for these products, which leads to more profit of these manufacturers [6]. Therefore, more and more manufacturers take part in designing socially responsible business operation [7,8]. For example, in China, Volkswagen launched "Child Safety Action" to promote consumers to use child safety seats; HP has become the first batch enterprises to implement an environmental management system (EMS) to save energy and recycle used products, and has become one of the international enterprises certified by ISO 14001.…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturers may engage in multiple dishonest behaviors, which primarily include fraud, the misuse of eco-labels, and the use of counterfeit products. These issues are the subject of longterm research, as the problem is global (Hamilton and Zilberman, 2006;Lee et al, 2018). Ibanez and Grolleau (2008) proposed that a polluting firm may also claim eco-labels by paying a fee because consumers cannot observe production technology or pollution related to production.…”
Section: Manufacturers' Dishonest Behaviormentioning
confidence: 99%
“…Supporters of CSR suggest that investments in CSR activities are necessary for firms to undertake. Many studies have shown a positive relationship between CSR and corporate performance (Shen and Chang, 2008;Wang et al, 2008;Lee et al, 2018). Moreover, Heal (2005) suggested that externalization of part of the production cost is one of the reasons why some firms select to act irresponsibly.…”
Section: Introductionmentioning
confidence: 99%
“…Other views argue that CSR activities represent a costly diversion of limited resources. This view is discussed and studied by many researchers (see, for example, Brammer et al, 2005, Becchetti et al, 2007, Shen and Chang, 2008, Barnett, 2007, Wang et al, 2008, Lee et al, 2018.…”
Section: Introductionmentioning
confidence: 99%